Preparation, Crystal Structure, and Energetic Properties of Four 2,4,7,9-Tetranitro-10H-benzofuro[3,2-b]indole (TNBFI) Based Solvates - Yiru Chen; Mi Yan; Chunbo Shi; Peilin Yang; Jinkun Guo; Yu Liu; Shiliang Huang (Chemistry, 2025)
Understanding the reactivity and the crystallinity of energetic materials in a solvent is significantly important for their synthesis, purification, and recrystallization. Here, the recrystallization of TNBFI (2,4,7,9-tetranitro-10H-benzofuro[3,2-b]indole), a primary explosive with good thermal stability, in different solvents was studied. Four TNBFI solvates, including TNBFI·AC (AC = acetone), TNBFI·2DMSO (DMSO = dimethyl sulfoxide), TNBFI·4DIO (DIO = 1,4-dioxane), and TNBFI·ACN (ACN = acetonitrile), were obtained. The crystal structures of the solvates were determined by single-crystal X-ray diffraction (SCXRD). The molecular packing and intermolecular interactions in the solvate structures were investigated, and their energetic properties were predicted. Among them, TNBFI·ACN showed good detonation performance with a detonation velocity of 6228 m·s−1 and detonation pressure of 16.23 GPa, which was comparable to TNT and with a potential application in both ammunition and industry. These results will be helpful in the synthesis and purification of TNBFI and valuable for the design of the solvate structure for other energetic materials.